2011
DOI: 10.1051/0004-6361/201016251
|View full text |Cite
|
Sign up to set email alerts
|

Wavelengths and oscillator strengths of Xe II from the UVES spectra of four HgMn stars

Abstract: Aims. In spite of large overabundances of Xe ii observed in numerous mercury-manganese (HgMn) stars, Xe ii oscillator strengths are only available for a very limited number of transitions. As a consequence, several unidentified lines in the spectra of HgMn stars could be due to Xe ii. In addition, some predicted Xe ii lines are redshifted by about 0.1 Å from stellar unidentified lines, raising the question about the wavelength accuracy of the Xe ii line data available in the literature. For these reasons we in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…λ4180, λ4208, λ4245, λ4330, λ4462 Å) show a ∼ 0.1 Å blue shift, which indicates that we see different isotopes at once, similar to the case of helium. The radial velocity shift of the lines corresponds to the isotopic shifts observed in CP stars (Yüce et al, 2011). Past studies have reported Xe, Bi and other heavy elements in Feige 86 (Bonifacio et al 1995, Castelli et al 1997.…”
Section: Reanalysis With Tlusty/xtgridmentioning
confidence: 63%
“…λ4180, λ4208, λ4245, λ4330, λ4462 Å) show a ∼ 0.1 Å blue shift, which indicates that we see different isotopes at once, similar to the case of helium. The radial velocity shift of the lines corresponds to the isotopic shifts observed in CP stars (Yüce et al, 2011). Past studies have reported Xe, Bi and other heavy elements in Feige 86 (Bonifacio et al 1995, Castelli et al 1997.…”
Section: Reanalysis With Tlusty/xtgridmentioning
confidence: 63%
“…When no data are found in the database, we use log gf values given in the VALD3 database (Ryabchikova et al 2015) (Mn II, Fe III, and Ni II). We can find no data of atomic transition probabilities for two ions Ga II and Xe II in these databases and use data taken from Hubrig et al (2014) and stellar log gf values given in Yüce et al (2011), respectively. Effects of isotopic or hyperfine structures for Mn II, Ga II, and Hg II have not been taken into acount in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We identified the stellar lines with the help of the general references A Multiplet Table of Astrophysical Interest (Moore, ) and Wavelengths and Transition Probabilities for Atoms and Atomic Ions, Part 1 (Reader & Corliss, ) as well as Pettersson () for S II, Huldt, Johansson, Litzen, and Wyart () for Ti II, Catalan, Meggers, and Garcia‐Riquelme () for Mn I, Iglesias and Velasco () for Mn II, Nave, Johansson, Learner, Thorne, and Brault () for Fe I, and Dworetsky (), Johansson (), Guthrie (), and Adelman () for Fe II, Nilsson, Johasson, and Kurucz () for Y II, and Yüce, Castelli, and Hubrig () for Xe II. The spectrum of HR 196 exhibits lines of CI, Mg II, AlI, Si II, Ca I, Ca II, Sc II, Ti II, V II, Cr I, Cr II, Mn I, Fe I, Fe II, NiI, Ni II, Sr II, and Ba II.…”
Section: Measurement Of the Spectrogramsmentioning
confidence: 99%
“…It includes for each line the multiplet number (Moore, ), the laboratory wavelength, the logarithm of the gf‐value and its source, the equivalent width (in mÅ) as observed, and the deduced abundance. For some species, letters replace multiplet numbers to indicate sources other than Moore (): I, Iglesias and Velasco (); J, Johansson (); K, Kurucz and Bell (); and Y, Yüce et al (). For comparison purpose, we used the solar values of Asplund et al (), Grevesse, Scott, Asplund, and Sauval (), and Scott et al (, ).…”
Section: Abundance Analysesmentioning
confidence: 99%
See 1 more Smart Citation